BIOGRAPHY OR A DECLARATION OF PHILOSOPHICAL AMBITION: HOW TO READ ECCE HOMO BY NIETZSCHE - Lúcia Schneider Hardt (Editora da Universidade de Santa Cruz do Sul, 2015)
This article discusses the book Ecce homo, by Nietzsche, defending that the text is an interpretation of the philosopher himself on her own thought, not to give the book a sacred tone, nor to stress his biography, but affirming a dissonant thought that indicates his philosophical ambition. With no constraints, Nietzsche presents his conflicts, passions, deceptions, announcing a tragic dimension of life that is not guided by pessimism, but by happiness of living intensely, understanding suffering as one of the facets of life. His philosophy derives from a life demand, transfigured by an experience that promotes self cultivation and the possibility of "becoming what one really is" through the "applying" of one's own genealogic method.